2000
DOI: 10.1034/j.1600-0706.2000.900103.x
|View full text |Cite
|
Sign up to set email alerts
|

Flood disturbance, algal productivity, and interannual variation in food chain length

Abstract: Marks, J. C., Power, M. E. and Parker, M. S. 2000. Flood disturbance, algal productivity, and interannual variation in food chain length. -Oikos 90: 20 -27.The length of a river food chain changed from year to year, shifting with the hydrologic regime. During drought years, grazers suppressed algae across a nutrient gradient, while predators were functionally unimportant. Following flood disturbance, predators suppressed grazers, releasing algae. These results suggest that hydrologic regime, rather than produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 26 publications
7
74
0
3
Order By: Relevance
“…It is well known that floods can reduce the abundance of stream invertebrates directly (Matthaei and Townsend 2000), and that populations can recover rapidly if predation pressure and competition are reduced (Scrimgeour et al 1988;Zhang et al 1998). Thus, biological interactions may be particularly important in structuring many stream communities during more stable periods (Power 1990;Marks et al 2000). However, recent studies indicate that biotic interactions may be just as important in disturbed environments (Wootton et al 1996;Thompson et al 2002).…”
Section: Introductionmentioning
confidence: 92%
“…It is well known that floods can reduce the abundance of stream invertebrates directly (Matthaei and Townsend 2000), and that populations can recover rapidly if predation pressure and competition are reduced (Scrimgeour et al 1988;Zhang et al 1998). Thus, biological interactions may be particularly important in structuring many stream communities during more stable periods (Power 1990;Marks et al 2000). However, recent studies indicate that biotic interactions may be just as important in disturbed environments (Wootton et al 1996;Thompson et al 2002).…”
Section: Introductionmentioning
confidence: 92%
“…Menge and Sutherland, 1976); however, empirical tests of disturbance impacts on food chain length in streams have yielded contrasting results, reflecting different approaches, methodologies and focal disturbance regimes. Flood disturbances have reportedly increased (Marks et al, 2000), decreased (Parker and Huryn, 2006) or not affected (Townsend et al, 1998) food chain length in streams. Drought disturbance studies have been slower to emerge, revealing reductions in food chain length where dewatering occurs Sabo et al, 2010), or no change where flow reduction is less severe (Walters and Post, 2008).…”
Section: P0575mentioning
confidence: 99%
“…Fish effects depend on a variety of other factors, especially when food web linkages are between pelagic fish and benthic invertebrates and algae. For instance, Marks et al (2000) demonstrated that importance of fish predation is dependent on functional food chain length, which is affected by disturbance (flooding), but also that fish effects on herbivores are influenced by specific herbivore habits (i.e., highly mobile grazers versus restricted mobility grazers). Fish predation effects are also dependent upon behavior of grazers, which can change in the presence or absence of predation (McIntosh & Townsend, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Recent food web studies have shown this to be a simplified view, with complex trophic interactions and resource limitation also being important, but this is still a useful heuristic framework (Polis & Winemiller, 1996). Studies have demonstrated that predators and herbivores can affect abundance and diversity of lower trophic levels in a variety of aquatic habitats (Power et al, 1985(Power et al, , 1988Threlkeld, 1988;Power, 1990;Martin et al, 1992;Rosemond et al, 1993;Bro¨nmark, 1994;Wootton, 1995;Marks et al, 2000), but no studies have yet addressed trophic interactions between vertebrates and invertebrates on stromatolites.…”
Section: Introductionmentioning
confidence: 97%